Estimating the western North Atlantic Subtropical Gyre zonal currents in 2021 through single- and three-box inverse models - Santana Toscano, Daniel; Pérez-Hernández, M. Dolores; Arumí Planas, Cristina; Hernández-Guerra, Alonso (Progress in Oceanography, 2025)
The western North Atlantic Subtropical Gyre comprises the warm Gulf Stream (GS) and the cold Deep Western Boundary Current (DWBC), which are the main currents of the Atlantic Meridional Overturning Circulation (AMOC). Hydrographic sections conducted at 66°W (A22) and 52°W (A20) in the western North Atlantic Subtropical Gyre (NASG) have sampled these currents in 1997, 2003, 2012, and 2021. Both single- and three-box inverse models are used to compute mass, heat, and freshwater transport to the hydrographic data of 2021 with no significant differences between methodologies. This study reveals a substantial change in the GS mass transport at both 52°W and 66°W in spring 2021 compared to spring 2012 and summer 1997, but no changes compared to fall 2003. Conversely, the DWBC shows no significant modification between spring 2021 and previous cruises. Moreover, the North Brazil Current mass transport, which is sampled by the A20 section, presents the downstream weakening showcased previously. Heat and freshwater fluxes are not significantly different from zero, therefore the water volumes enclosed by the A20 and A22 sections do not reflect a net air-sea flux in 2021. Although the GS exhibits interdecadal variability, the lack of other changes over time in this area suggests a general stability in the environmental and forcing conditions. This study highlights the consistent mass transports of the main AMOC currents in the western NASG, particularly the GS and DWBC, emphasizing their stability and importance in broader climate and oceanographic processes. 16